Analisis Nilai Kerukunan dalam Tradisi Kupatan pada Masyarakat Islam di Pesisir Desa Sedayulawas, Lamongan - Rizki Dwi Septian Rizky (Indonesian Journal of Humanities and Social Sciences, 2023)
The Kupatan tradition is one of the cultural heritages that has become an integral part of the life of the Islamic community in the coastal village of Sedayulawas Lamongan. This article aims to explore and analyze the values of harmony embedded in the Kupatan tradition and its impact on social unity and local community cohesion. The research method used is qualitative research with an ethnographic approach. Data were collected through participatory observation, in-depth interviews, and documentation studies. Data analysis was conducted using an inductive approach to identify the values of harmony that emerged in organizing Kupatan. The results show that the Kupatan tradition in Sedayulawas Village is a ritual event and an expression of the profound importance of unity in the local Islamic community. Values such as helping, respecting each other, solidarity, and brotherhood are evident in implementing Kupatan. This article has significant implications for cultural preservation and community development in the coastal areas of Sedayulawas Village and its surroundings. By understanding and appreciating the values of harmony in the Kupatan tradition, communities can strengthen their social relationships and promote peace and stability in their neighborhoods. In addition, this article also provides valuable insights into how local cultural values can be integrated into sustainable development at the local and national levels.